Bode, Barbara. The bells of silence. Destruction and creation in the Andes. Lima: Fondo Editorial del Congreso del Perú, 2015, 521 pp. - Donayre Miranda, Fabio (2016)
Reviews the book's argument highlighting the ways in which political, ecclesial and cultural circumstances shaped the interpretation that the population of Huaraz gave to the disaster unleashed by the 1970 earthquake in the Huaylas alley.